Educational Model: Anti-Stroke Gymnastics on Compliance and Health Status of Patients Hypertension - Manurung, Santa (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: The prevalence of hypertension continues to increase, various epidemiological studies show an increase in the incidence and prevalence of hypertension in various parts of the world. According to the American Heart Association (AHA), the American population aged over 20 years suffering from hypertension has reached up to 74.5 million people, but almost 90% of cases have no known cause. Hypertension is a silent killer where the symptoms can vary in each individual and are almost the same as the symptoms of other diseases. In Indonesia, the problem of hypertension is a big challenge, because hypertension is very often found in primary health services with a high prevalence. Hypertension if not handled properly can cause damage to blood vessels throughout the body and the most obvious is the risk of damage to the brain, eyes, heart, and kidney disease. These risks can be avoided and minimized by pharmacological and non-pharmacological management. Anti-stroke exercise is one of the gymnasticsthat is useful to prevent the risk of stroke in someone who suffers from hypertension. This research is a quasi experiment with pre-post test with control group design. This study aims to determine the effect of anti-stroke gymnastics education on adherence and health status of patients with hypertension. The sampling technique was simple random sampling and the determination of the sample size was using the hypothesis test of the average difference in two independent groups. Data processing and analysis in this study used paired t-test and independent t-test. The results showed that there were significant differences in knowledge, patient compliance, decreased blood pressure and health status of hypertension patients after anti-stroke gymnastics was performed. It is recommended that anti-stroke gymnastics can be used as a non-pharmacological therapy to treat hypertension patients to prevent stroke.